Alcohol hangover: The health impact with a historic and Chinese perspective. (February 2020) - Nutt, Prof David; Liu, Yuan-Cai; Chen, Mo-Si; Wang, De-Liang; Palmer, Emily; Tyacke, Robin
Hangovers represent a major source of distress to the individual and a huge source of economic loss to society. Hangovers and their associated problems have been recognised for thousands of years in both Western and Eastern cultures but only in recent years has there been any scientific research into their mechanisms and treatments. This small review contrasts Chinese and Western approaches to the question of hangovers. We also give an overview of recent research into the mechanisms that may underpin it, which may suggest new approaches to prevention or treatment of hangovers.